(untitled) - Zhang, Zili (Berlin, 2004)
This is book introduce about fundamentals of hybrid intelligant systems and agents, methodology and framework, application system, concludung remarks
Mô hình hóa trong quản lý đất đai
Keywords: Intelligent agents (Computer software),Expert systems (Computer science),Soft computing,Hệ thống thông minh ( phần mềm máy tính ),Chuyên gia hệ thống ( khoa học máy tính ),Tin học mềm